2022
DOI: 10.3390/cells11162525
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Multimodal Metabolomics Investigation of the Haemonchus contortus Exsheathment Secretome

Abstract: In nematodes that invade the gastro-intestinal tract of the ruminant, the process of larval exsheathment marks the transition from the free-living to the parasitic stages of these parasites. To investigate the secretome associated with larval exsheathment, a closed in vitro system that effectively reproduces the two basic components of an anaerobic rumen environment (CO2 and 39 °C) was developed to trigger exsheathment in one of the most pathogenic and model gastrointestinal parasitic nematodes, Haemonchus con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…The separation and detection of metabolites were performed using the Waters2D UPLC tandem Q Exactive HF high-resolution mass spectrometer. For detailed statistical tests performed during microbiome analysis, refer to the works of Palevich et al [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The separation and detection of metabolites were performed using the Waters2D UPLC tandem Q Exactive HF high-resolution mass spectrometer. For detailed statistical tests performed during microbiome analysis, refer to the works of Palevich et al [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that specific to L3 are nicotinic acid and branched-chain and aromatic amino acids (BCAA). The recent metabolomics studies showed that BCAA are positively related to longevity common to Dauer in C. elegans and Haemonhus contortus during mitochondrial biogenesis in ensheathment eggs ( Palevich et al, 2022 ). In this study, BCAA were only identified in L3 stage, which like a Dauer stage, uses endogenous energy sources.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, parasitic nematode research increasingly relies on metabolomics techniques due to its immense potential applications in studying these organisms effectively. The gastrointestinal tract is a dynamic metabolic and immunologically active ecosystem, and its complete set of metabolites reflects both the enzymatic pathways of host and gut inhabitants and the complex network that connects them ( Palevich et al, 2021 , 2022 ; Whitman et al, 2021 ). The use of metabolomics is particularly suited to understanding nematode metabolism, including the identification of novel drug targets, differences between developmental stages, and mechanisms involved in host-parasite interactions ( Jasmer et al, 2019 ; Molenaars et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Quality control and peak deisotoping analysis were based on our previously published procedures ( 10 ). The details of extraction procedures, chromatographic gradients, and instrument settings have been previously described by Palevich et al ( 11 ). For each metabolomic data set, principal component analysis (PCA) was performed on the log 10 intensities for raw chromatographic peaks to assess similarity and separation of DRF fractions.…”
Section: Announcementmentioning
confidence: 99%